2016
DOI: 10.1597/14-269
|View full text |Cite
|
Sign up to set email alerts
|

Adults’ Narratives of Growing up with a Cleft Lip and/or Palate: Factors Associated with Psychological Adjustment

Abstract: Background Growing up with a cleft lip and/or palate presents a number of challenges for those affected and their families. Understanding why some individuals cope well while others struggle is key to psychological research in this field. A better appreciation of the factors and processes that contribute to psychological adjustment to cleft lip and/or palate (CL/P) from the patient perspective would be of value to both researchers and clinicians. Design Qualitative data elicited from individual interviews with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
50
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 86 publications
7
50
2
Order By: Relevance
“…Our findings contrast to the results published by Stock et al, who observed no negative effect of facial clefts on social integration or on initiation of a romantic relationship [13]. Another recent investigation by Stock et al revealed that study participants perceived a deficit of awareness and understanding of cleft patients among the general population, however [12]. There are, indeed, still indications of difficult adjustment of cleft patients to their environment and the presence of psychosocial barriers in society.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings contrast to the results published by Stock et al, who observed no negative effect of facial clefts on social integration or on initiation of a romantic relationship [13]. Another recent investigation by Stock et al revealed that study participants perceived a deficit of awareness and understanding of cleft patients among the general population, however [12]. There are, indeed, still indications of difficult adjustment of cleft patients to their environment and the presence of psychosocial barriers in society.…”
Section: Discussioncontrasting
confidence: 99%
“…There are reports of social rejection in school and daily life. Cleft patients have reported that they have been teased because of their facial anomaly [10][11][12]. In contrast, a recent study found that adults born with a cleft do not report a relevant effect of their facial malformation on social and romantic relationships [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, Kapp-Simon et al (2015) recently demonstrated that patient participation in decisions explained a significant amount of the variance in patients' satisfaction with outcomes. Furthermore, in a study to identify factors affecting psychological adjustment to their clefts, adult patients with CLCP recalled traumatic experiences as children, wherein their opinions about additional surgery were not considered (Stock et al, 2016). Prior work has also shown that correlation between patients' and caregivers' desire for revision surgeries, such as lip revision or rhinoplasty, is low, which we similarly found from our analysis (Ranganathan et al, 2016).…”
Section: Discussionsupporting
confidence: 66%
“…Of course, visible facial difference as a broader category has been taken up as a research topic in the emerging field of the psychology of appearance (Lansdown et al 1997;Rumsey and Harcourt 2012). Research conducted under this heading, however, tends to highlight the psycho-social issues associated with facial variance, for instance depression, social anxiety, or avoidance behavior (Koster and Bergsma 1990;Macgregor 1970;Rumsey and Harcourt 2004;Stock, Feragen, and Rumsey 2016;Thompson and Kent 2001;Valente 2009). By focusing on the psychological condition of those who have a different face, this approach has a rather narrow view on the social context informing their experiences.…”
Section: Introductionmentioning
confidence: 99%